Percepção dos consumidores de diferentes culturas em relação à estratégia de storytelling - Andriolo, Gabriela Comparin (My University, 2019)
The way companies are communicating with their customers has been changing, once traditional advertising pieces, in the face of a world filled with information, are no longer able to hold the public's attention. Therefore, it is necessary to look for ways that meet the demands of the current world and that are capable of creating links between brand and consumer. In this context, the strategy of storytelling has been a promising and effective alternative to create connections that support business. Thus, the present study analyzes the perception Brazilians and North Americans in relation to the strategy of storytelling in the promotion of brands and products. For this purpose, a descriptive quantitative research was applied, with descriptive and variation analyzes. There were 178 valid cases distributed between the two countries (86 Brazilians and 92 North Americans). The results showed that Americans are significantly more attracted by the advertisement that Brazilians and they also have higher averages for engagement and purchase intention. However, Brazilians showed a higher level of positive attitude toward the advertisement than Americans.(sic)
A maneira em que as empresas estão se comunicando com seus clientes vem sendo modificada, uma vez que as peças publicitárias tradicionais, diante de um mundo farto de informações, já não são capazes de prender a atenção do público. Portanto, se faz necessário buscar formas que atendam a demanda do mundo atual e que sejam capazes de criar vínculos entre marca e consumidor. Neste contexto, a estratégia de comunicação storytelling vêm sendo uma alternativa promissora e eficaz para criar conexões que amparam negócios. Desta forma, o presente trabalho analisa a percepção dos consumidores brasileiros e norte-americanos em relação à estratégia de storytelling na divulgação de marcas e produtos. Para tanto, foi aplicada uma pesquisa quantitativa de caráter descritivo, com análises descritivas e de variância. Foram obtidos 178 casos válidos distribuídos entre os dois países (86 brasileiros e 92 norte-americanos). Os resultados apontaram que os norte-americanos são significantemente mais atraídos pelo anúncio do que os brasileiros e também possuem médias mais altas com relação ao engajamento e intenção de compra. No entanto, os brasileiros demonstraram um nível de atitude positiva mais alto frente ao anúncio que os norte-americanos.(sic)
Keywords: Consumidores; Cultura; Comportamento do consumidor